2014
DOI: 10.1002/cncy.21512
|View full text |Cite
|
Sign up to set email alerts
|

Combination of p16INK4a/Ki67 immunocytology and hpv polymerase chain reaction for the noninvasive analysis of HPV involvement in head and neck cancer

Abstract: BACKGROUND: High-risk human papillomavirus (HPV) infection has been identified as a relevant risk for the development of head and neck squamous cell carcinomas (HNSCCs). As HPV status has also gained a role as a prognostic and predictive biomarker for this entity, there is a growing demand for valid HPV testing in HNSCC patients METHODS: Liquid-based cytological smears from 45 HNSCC and 20 control patients were collected and used for simultaneous immunocytochemi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 41 publications
2
24
0
1
Order By: Relevance
“…We recently read an interesting article by Linxweiler et al, who reported the use of p16‐Ki67 immunocytochemistry combined with human papillomavirus (HPV) testing on cytological specimens for the assessment of HPV involvement in head and neck squamous cell carcinoma (HNSCC) . Their findings regarding brush cytology and HPV testing are in agreement with the results of our previous study .…”
supporting
confidence: 88%
See 1 more Smart Citation
“…We recently read an interesting article by Linxweiler et al, who reported the use of p16‐Ki67 immunocytochemistry combined with human papillomavirus (HPV) testing on cytological specimens for the assessment of HPV involvement in head and neck squamous cell carcinoma (HNSCC) . Their findings regarding brush cytology and HPV testing are in agreement with the results of our previous study .…”
supporting
confidence: 88%
“…Linxweiler et al found a very high sensitivity (98%) and specificity (100%) for head and neck brush cytology, although the estimation of sensitivity based on an analytic population that was composed mostly of patients with cancer (50 of 65 patients) has to be regarded with caution . In fact, a recent work highlighted that disease prevalence affects test characteristics, including sensitivity .…”
mentioning
confidence: 99%
“…To determine the involvement of HPV in the carcinogenesis of the HNSCC and CUP patients, we used a combination of HPV-DNA-PCR and a simultaneous immunohistochemical detection of p16 and Ki67 as recently described [52]. …”
Section: Methodsmentioning
confidence: 99%
“…When testing for p16 and HPV, the two tests are not always concordance with each other (around 81.0%‐94.6%) . It has been suggested that performing combination testing of p16 and HPV status together may improve prognostic accuracy …”
Section: Biomarkers In Hnscc Tumor Tissuesmentioning
confidence: 99%